PENGARUH KEMAMPUAN BERWIRAUSAHA DAN KEPRIBADIAN TERHADAP PENGEMBANGAN KARIR INDIVIDU PADA MEMBER PT. IFARIA GEMILANG (IFA) DEPOT SUMATERA JAYA MEDAN - Rindi Andika (JUMANT, 2017)
Imaging is one of the most important elements that should be owned by every agency of Individual career development is needed so that the workers have a career that continues to increase. For someone who works in a company does not just want to earn money for the necessities of life, but also want a good career achievement. To find it, to do further research. In reaching a career, one must have a strong ability and a good personality. Because career will not be achieved with the capability that's it. The problems in this study is whether entrepreneurship skills and influential personalities either partially or simultaneously on individual career development. This study aims to reveal the influence of entrepreneurship skills and personality of the individual career development as well as implement and compare the theory that writers get the actual situation on the ground. This research was conducted on a member of PT. Ifaria Gemilang (IFA), Medan Jaya Depot Sumatra with 78 respondents. The object of research is a distributor company based in Bogor, Indonesia, which was founded by Tanu Sutomo and Djarot Widjanarko in 1990. The data was collected through questionnaires. Data analysis method used is quantitative/associative with the SPSS (Statistical Product and Service Solution) ver. 16.0 and data analysis techniques using multiple regression analysis. And tests conducted in this study is the quality of the data test (validity and reliability), classicalassumption (normality test, multicollinearity and heterokedastisitas) and conformance test (Test Goodnees Of Fit) consisting of a t-test, F and test of determination.